Biobank of Cells, Tissues and DNA from Patients with Neuromuscular Diseases: An Indispensable link between Clinical Centers and the Scientific Community. (13th February 2017) - Mora, Marina; Bragato, Cinzia; Gibertini, Sara; Zanotti, Simona; Curcio, Maurizio; Canioni, Eleonora; Salerno, Franco; Blasevich, Flavia; Saredi, Simona; Ruggieri, Alessandra; Pasanisi, Maria Barbara; Bernasconi, Pia; et al.
The Biobank was established in 1986 as part of the routine diagnostic activity of the Division of Neuromuscular Diseases and Neuroimmunology, of the Carlo Besta Neurological Institute. It stores muscle tissue, cells and DNA from patients with neuromuscular diseases. The biobank provides samples as a service to the scientific community conducting research on neuromuscular disorders. Samples are from patients affected by different forms of muscular dystrophy, including the severe congenital and Duchenne muscular dystrophies, as well as limb girdle muscular dystrophies, congenital myopathies, distal and myofibrillar myopathies, inflammatory myopathies, and metabolic myopathies. Different types of biomaterials are frequently available from a single patient. The Biobank is founding partner of the EuroBioBank network, the first operating network of biobanks for rare diseases in Europe, and of the Italian Telethon Network of Genetic Biobanks. The involvement of the biobank into both networks has been instrumental for standardization of procedures and activities, implementation of sample access policies, and compliance with ELSI requirements. The biobank, with about 13000 biospecimens stored in total at the time of writing, constitutes a key source of biological samples for researchers worldwide.